The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1080/10673220802073956
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Intervention with Young Anxious Children

Abstract: Despite evidence that preschool and early elementary school-age children can present with anxiety disorders that may put them at risk for later psychopathology and dysfunction, the cognitive-behavioral protocols available for treating anxiety in children have been tested almost exclusively in older children. However, there could be benefits to treating children earlier, before anxiety disorders begin to impair their social and academic development. This report discusses the adaptations necessary in providing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 64 publications
0
47
0
1
Order By: Relevance
“…This information has clinical implications in that it may inform the selection of children for preventive or early intervention efforts, such as those developed by Rapee, Kennedy, Ingram, Edwards, and Sweeney (2005) and Hirshfeld-Becker, Masek, et al (2008) for childhood anxiety disorders, and those developed by Beardslee et al (1997) and Beardslee, Gladstone, Wright, and Coope (2003) and Clarke et al (2001) for major depressive disorder. It also highlights the importance, when evaluating children for anxiety disorders, of examining parental lifetime history of anxiety and mood disorders in understanding the child's prognosis.…”
Section: Discussionmentioning
confidence: 97%
“…This information has clinical implications in that it may inform the selection of children for preventive or early intervention efforts, such as those developed by Rapee, Kennedy, Ingram, Edwards, and Sweeney (2005) and Hirshfeld-Becker, Masek, et al (2008) for childhood anxiety disorders, and those developed by Beardslee et al (1997) and Beardslee, Gladstone, Wright, and Coope (2003) and Clarke et al (2001) for major depressive disorder. It also highlights the importance, when evaluating children for anxiety disorders, of examining parental lifetime history of anxiety and mood disorders in understanding the child's prognosis.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that children with more extreme BI or children with BI who also had parents with anxiety disorders might have been more likely to maintain their BI status over time and therefore provided a better test of this research question. Subsequent studies currently under way in our laboratory [Hirshfeld-Becker et al, 2006, 2008a and others may shed further light on this question.…”
Section: Can Bi Usefully Inform Preventive Intervention?mentioning
confidence: 93%
“…A clear relationship between BI and SOP has been established empirically. 42,43 In one study, children classified as BI at age 21 months and 31 months were significantly more likely to have SOP diagnosed at age 13 (61%) compared with those who had not been classified as BI (27%). 22 Another study found that 17% of 2-, 4-, and 6-year-olds classified as BI also met criteria for SOP, whereas there was no relationship between BI and other mood or anxiety disorders.…”
Section: Comorbiditymentioning
confidence: 96%